Estimation of evapotranspiration using Bowen ratio method. Issue 17 (2018) - Buttar, Noman Ali; Yongguang, Hu; Shabbir, Abdul; Lakhiar, Imran Ali; Ullah, Ikram; Ali, Asad; Aleem, Muhammad; Yasin, Muhammad Asim
Abstract: Evapotranspiration (ET) or water loss to the atmosphere is one of the most significant parts of the hydrologic cycle, and its estimation is subjected to uncertainties. Therefore, Calculation of the ET is an integral part of agricultural water management in local, regional and global water balance studies. In this study Bowen ratio method is used for measuring, deriving, and estimating input parameters for the estimation of ET for the whole cropping season for tea canopy, one month data is presented here. Results depicted the maximum and minimum estimated ET as 7.44 mmday- 1 and 0.12 mmday- 1 respectively. The overall estimated ET for the whole month was 3.423633 mmday- 1 . The estimated ET will be compared and calibrated against direct ET estimation method (i.e. eddy covariance) for the whole cropping season and further predictions will be provided about the implementation of this method for other crops as well.